Use of implementation science to advance family planning programs in low- and middle-income countries: A systematic review - Baynes, Colin; Steyn, Petrus; Soi, Caroline; Dinis, Aneth; Tembe, Stelio; Mehrtash, Hedieh; Narasimhan, Manjulaa; Kiarie, James; Sherr, Kenneth (Frontiers in Global Women's Health, 2022)
Objective As environmental and economic pressures converge with demands to achieve sustainability development goals, low- and middle-income countries (LMIC) increasingly require strategies to strengthen and scale-up evidence-based practices (EBP) related to family planning (FP). Implementation science (IS) can help these efforts. The purpose of this article is to elucidate patterns in the use of IS in FP research and identify ways to maximize the potential of IS to advance FP in LMIC. Design and methods We conducted a systematic review that describes how IS concepts and principles have been operationalized in LMIC FP research published from 2007–2021. We searched six databases for implementation studies of LMIC FP interventions. Our review synthesizes the characteristics of implementation strategies and research efforts used to enhance the performance of FP-related EBP in these settings, identifying gaps, strengths and lessons learned. Results Four-hundred and seventy-two studies were eligible for full-text review. Ninety-two percent of studies were carried out in one region only, whereas 8 percent were multi-country studies that took place across multiple regions. 37 percent of studies were conducted in East Africa, 21 percent in West and Central Africa, 19 percent in Southern Africa and South Asia, respectively, and fewer than 5 percent in other Asian countries, Latin America and Middle East and North Africa, respectively. Fifty-four percent were on strategies that promoted individuals' uptake of FP. Far fewer were on strategies to enhance the coverage, implementation, spread or sustainability of FP programs. Most studies used quantitative methods only and evaluated user-level outcomes over implementation outcomes. Thirty percent measured processes and outcomes of strategies, 15 percent measured changes in implementation outcomes, and 31 percent report on the effect of contextual factors. Eighteen percent reported that they were situated within decision-making processes to address locally identified implementation issues. Fourteen percent of studies described measures to involve stakeholders in the research process. Only 7 percent of studies reported that implementation was led by LMIC delivery systems or implementation partners. Conclusions IS has potential to further advance LMIC FP programs, although its impact will be limited unless its concepts and principles are incorporated more systematically. To support this, stakeholders must focus on strategies that address a wider range of implementation outcomes; adapt research designs and blend methods to evaluate outcomes and processes; and establish collaborative research efforts across implementation, policy, and research domains. Doing so will expand opportunities for learning and applying new knowledge in pragmatic research paradigms where research is embedded in usual implementation conditions and addresses critical issues such as scale up and sustainability of evidence-informed FP interventions. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/, identifier: CRD42020199353.